Identification of new sources of resistance to Striga gesnerioides in cowpea germplasm. Issue 3 (3rd April 2013) - Tignegre, Jean‐Baptiste S.; Ouedraogo, Jeremy T.; Melis, Rob; Tongoona, Pangirayi; Sibiya, Julia; Makanda, Itai; Drabo, Issa; Varshney, R.
Abstract There have been reports of breakdown of striga resistance in previously resistant cowpea cultivars in Burkina Faso. This could be attributed to new striga races emerging or to an increase in the aggressiveness of current striga races. Therefore, cowpea genotypes were evaluated in fields infested with S. gesnerioides at three striga hot spots in Burkina Faso and in pots under artificial infestation with striga races SR 1, SR 5 and SR Kp to identify new, adapted and striga‐resistant sources. Cowpea genotypes showed differential reactions for striga resistance over sites and for striga races in pot experiments, indicating differences in the races involved, and SR Kp was reported as a new race. Resistant sources conferring site‐specific or multiple striga‐race resistance were identified. Genotypes 58‐57, Sanga 2, IT84S‐2049, IT98K‐205‐8, IT93K‐693‐2, KVx771‐10, KVx775‐33‐2, KVx61‐1, Gorom local, Mouride and Melakh conferred resistance to all three striga races. These genotypes are potential donor parents for breeding new, adapted and striga‐resistant genotypes. Cowpea landraces including Moussa local and Niaogo local with farmers' preferred traits were susceptible and need improvement for striga resistance.